High-Velocity Clouds - Woerden, Hugo.; Wakker, Bart P.; Schwarz, Ulrich J.; Boer, Klaas S.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
This book contains 17 chapters reviewing our knowledge of the high-velocity clouds (HVCs) as of 2004, bringing this together in one place for the first time. Each of the many different aspects of HVC research is addressed by one of the experts in that subfield. These include a historical overview of HVC research and analyses of the structure and kinematics of HVCs. Separate chapters address the intermediate-velocity clouds, the Magellanic Stream, and neutral hydrogen HVCs discovered in external galaxies. Reviews are presented of the Ha emission and of optical and UV absorption-line studies, followed by discussions of the hot Galactic Halo and of the interactions between HVCs and their surroundings. Four chapters summarize the ideas about the origin of the high-velocity gas, with detailed discussions of connections between HVCs and the Galactic Fountain, tidally-stripped material, and remnants of the Milky Way's formation. A chapter outlining what we do not know completes the book. The book comes at a time when knowledge and understanding of the HVCs are making rapid progress, owing to technological, observational, and theoretical developments.
History of HVC research - an Overview -- HVC/IVC Maps and HVC Distribution Functions -- Kinematics of HV and IV Gas -- Interemdiate-velocity Clouds -- HVCS Related to the Magellanic System -- High-velocity Hi Gas in External Galaxies -- The Large- and Small-scale Structure of HVCs -- Ionized Gas Associated with HVCs -- The Coldest Phase in Halo High-velocity Gas: Dust and Molecules -- Distances and Metallicities of HVCS -- The Hot Halo -- HVCS Interacting With Their Environment -- Warps, Polar Rings and High-velocity Clouds -- High-Velocity Clouds: The Missing Link? -- Compact, Isolated High-velocity Clouds -- The Origin of the High-velocity Clouds -- Unsolved Mysteries of High-velocity Clouds.
Keywords: PHYSICS; ASTRONOMY; ASTROPHYSICS; PHYSICS; ASTRONOMY, ASTROPHYSICS AND COSMOLOGY; EXTRATERRESTRIAL PHYSICS, SPACE SCIENCES